Social Media and Life Partner Selection Behaviour among Undergraduate Students Unsure about who to Date in a Public University in Ghana (Global Journal of Human-Social Science, 2025)
Background: Ghana was home to 7.95 million social media user identities in January 2025 which is equivalent to 22.9% of the total population at the start of 2025. So far, from June 2024 - June 2025, the dominant platform was Facebook (39.44%) followed by YouTube (13.2%), then, Pinterest (10.68%), and the least was LinkedIn 1.46%. Objective: In view of this, the current study aimed to investigate how social media influence life partner selection behaviour among undergraduate students unsure about who to date in a public university in Ghana. Methods: Cross-sectional descriptive design was employed for the study and made used of interpretivists worldview. Data were solicited from ten (10) participants age between 18 and 24years old who voluntarily own out to share their views. The choice of the study population was supported by saturation theory. Interpretive phenomenological approach (IPA) was used to analyse the data. Results: The study found that participants experienced varied forms of social media influence on their life partner selection behaviour which often stem from confusion, erratic decisionmaking, social pressure, boundary erosion, physical appearance, social status, popularity, and lifestyle portrayals on social media. Conclusion: Parents should endeavour to restrict their wards from navigating social media platforms in order for them to have a sound mind to think about who to choose as a life partner. Also, participants must uphold the virtue of conscientiousness in order to desist from navigating social media platforms in their life and should not depend solely on social media to select a life partner.